Facile synthesis of 3D porous Co3V2O8 nanoroses and 2D NiCo2V2O8 nanoplates for high performance supercapacitors and their electrocatalytic oxygen evolution reaction properties. Issue 10 (22nd February 2017) - Zhang, Jingchao; Yuan, Baiqing; Cui, Shufang; Zhang, Nana; Wei, Jingjing; Wang, Xiao; Zhang, Daojun; Zhang, Renchun; Huo, Qisheng
Abstract : Porous Co3 V2 O8 nanoroses and NiCo2 V2 O8 nanoplates served as effective electrocatalysts in the oxygen evolution reaction and as electrodes of supercapacitors. Abstract : Binary metal oxides have recently attracted extensive attention from researchers in the energy storage and conversion field due to their high energy densities and multiple oxidation states. Novel 3D Co3 V2 O8 porous rose-like structures and 2D NiCo2 V2 O8 nanoplates were facilely synthesized via a solvothermal method, and the morphologies, Ni/Co ratios, and surface area of these samples can be easily tuned in the same procedure. The as-prepared Co3 V2 O8 porous rose-like structure exhibited good electrocatalytic oxygen evolution performance with excellent activity and stability. In addition, 2D NiCo2 V2 O8 nanoplates delivered a high specific capacitance of 1098.9 F g −1 at 4 A g −1 and good cycling stability (remaining 68% after 7000 cycles) in aqueous KOH electrolyte. The NiCo2 V2 O8 nanoplates inherit the pseudocapacitive benefits of both Ni3 V2 O8 and Co3 V2 O8, showing a higher specific capacitance than pure Co3 V2 O8 porous rose-like structures.